Лізингова діяльність: історія виникнення та розвитку - Ніколаєва, С. П.; Пугаченко, О. Б.; Nikolaeva, S.; Pugachenko, O. (КНТУ, 2014)
У статті представлено авторське бачення етапів історії розвитку та поширення сучасного лізингу в світовій економіці (етап становлення лізингу в індустріально розвинених країнах; етап «лізингового буму» в розвинених індустріальних країнах та розповсюдження лізингу на ринки, що розвиваються; етап насичення, стабілізації, диверсифікації лізингу). Встановлено, що стадії існування лізингової індустрії передбачають: розвиток фінансової оренди; становлення лізингової індустрії; розвиток оперативного лізингу; розвиток конкуренції на ринку лізингу. The objectives of the article are to investigate history of the origin, development and existence of leasing activity in order to clarify the main stages and tendencies of its development and to improve understanding of the economic substance of leasing operations. The article presents the author's view on the development’s history and expansion of modern leasing in the global economy (leasing forming in industrialized countries; stage "of leasing boom" in the advanced industrial countries and asset distribution to emerging markets, stage of saturation, stabilization, diversification of asset). It has been ascertained that stages of the leasing industry include the development of a finance lease; establishment of the leasing industry; development of an operating lease; and development of competition in the leasing market etc.
Leasing Activity: History and Development
Keywords: історія; виникнення; розвиток; лізинг; оренда; лізингова діяльність; етапи; стадії; history; origin; development; leasing; renting; leasing activities; stages